Parandrinae (Coleoptera: Cerambycidae) from Colombia - CARDONA-DUQUE, JULIANA; SANTOS-SILVA, ANTONIO; WOLFF, MARTA (Revista Colombiana de Entomología, 2010)
The Parandrinae are a Cerambycidae subfamily with 63 described species, from which 45 occur in America. A total of 266 specimens collected in Colombia was examined, deposited in 17 Colombian collections and other museums in Brazil. Twelve species are reported, ten of them from the specimens examined and two from reports in the literature. Acutandra degeeri (Thomson, 1867), Acutandra punctatissima (Thomson, 1861) and Parandra ubirajarai (Santos-Silva, 2001) are excluded from the Colombian fauna. Depository institutions for some type specimens are corrected and characters that permit identifying the female of Acutandra ubitiara (Santos-Silva & Martins, 2000) are included. Identification keys are presented for the genera, subgenera and species of the Parandrinae present in Colombia. Distribution maps are included.